THE URGENCY OF ARTIFICIAL INTELLIGENCE REGULATION FROM A JOINT AUTHORSHIP PERSPECTIVE ON COPYRIGHT INFRINGEMENT - Subagiyo, Dwi Tatak; Wibisono, Hari (Faculty of Law, Universitas Lampung, 2024)
This research, titled Urgency of Artificial Intelligence Regulation from the Perspective of Joint Authorship Against Copyright Infringement, aims to analyze the legal framework governing Artificial Intelligence (AI)-based creations in Indonesia and explore the application of the Joint Authorship perspective to AI-generated works. Using a normative legal methodology, the research focuses on library research involving laws, regulations, and related literature. The findings reveal that Indonesia's Copyright Law No. 28 of 2014 does not adequately address AI-based creations. Specifically, Articles 58 and 59, which reference the